From craft to industry the ethnography of proto-industrial cloth production - Goody, Esther N.; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 1982)
The essays in this volume focus on two themes: the centrality of the production of and trade in cloth in the emergence of market activity; and the nature of the industrialization process. The core of the book is formed by four detailed ethnographic studies of the development and current organization of cloth production for the market, in different parts of the world: tailoring in Kano City, northern Nigeria (Pokrant); dyeing and weaving in Daboya, northern Ghana (Goody); 'fashion'- shirt production in Bombay, India (Swallow); and the manufacture of 'handmade' Harris tweed in the Hebrides (Ennew). Each study examines access to raw materials and to the market, relations of production, the investment of capital and the reproduction of the system. Individually, they raise such questions as the role of fashion, the effects of national economic policies and legislation, and factors related to the modification of traditional technologies.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Electronic books; Weavers; Industries, Primitive; Economic anthropology